PERFORMATIVITAS RITUAL MANGULOSI DALAM PERKAWINAN ADAT MASYARAKAT BATAK TOBA - Tama, Krisna; Lephen, Purwanto (Institut Seni Indoensia Surakarta, 2023)
ABSTRACTThe mangulosi ritual is part of the ulaon unjuk ritual ceremony in Toba Batak marriages. This research analyzes the performativity of the mangulosi ritual based on an